Longer Paced QRS Duration is Associated With Increased Prevalence of Right Ventricular Pacing‐Induced Cardiomyopathy. (19th August 2016) - KHURSHID, SHAAN; LIANG, JACKSON J.; OWENS, ANJALI; LIN, DAVID; SCHALLER, ROBERT; EPSTEIN, ANDREW E.; MARCHLINSKI, FRANCIS E.; FRANKEL, DAVID S.
Paced QRS and RV Pacing‐Induced Cardiomyopathy: Introduction: Pacing‐induced cardiomyopathy (PICM) is an important cause of heart failure in patients exposed to frequent right ventricular (RV) pacing. While echocardiography is diagnostic, the optimal surveillance strategy remains unknown. We sought to identify clinical and electrocardiographic factors associated with the presence of PICM to guide further testing. Methods and Results: We retrospectively studied 1, 750 consecutive patients undergoing pacemaker implantation 2003–2012. Patients were included if baseline LVEF was normal, single chamber ventricular or dual chamber pacemaker (but not ICD or cardiac resynchronization therapy device) was implanted, frequent (≥20%) RV pacing was present and repeat echocardiogram was available following implantation. PICM was defined as ≥10% decrease in LVEF, resulting in LVEF <50%. Patients with alternative causes of cardiomyopathy were excluded. Clinical and electrocardiographic indicators of PICM were identified using multivariate logistic regression. Of 184 patients meeting study criteria, 42 (22.8%) developed PICM, with decrease in mean LVEF from 62.1% to 35.3% over mean follow‐up 2.5 years. Longer follow‐up paced QRS duration was associated with the presence of PICM (multivariate odds ratio 1.34 per 10 millisecond increase, 95% CI 1.06‐1.63, p = 0.01). Paced QRS duration ≥150 milliseconds was 95% sensitive for PICM. Only half of patients with PICM had heart failure signs or symptoms at the time of echocardiographic diagnosis. Conclusion: Patients with frequent RV pacing and paced QRS duration ≥150 milliseconds should be screened by echocardiogram to assess for PICM. Patients with paced QRS duration <150 milliseconds likely do not require screening, in the absence of heart failure signs or symptoms.